2008
DOI: 10.1037/0735-7036.122.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Head rotations in the play of Hanuman langurs (semnopithecus entellus): Description and analysis of function.

Abstract: Although head rotations are frequent patterns in play behavior in many mammalian species and differ from head movements used in other contexts, they have not been quantitatively described and their function remains unclear. The head rotations occurring in the play behavior of free-ranging Hanuman langurs (Semnopithecus entellus) were described from videotaped sequences. The authors tested 2 possible hypotheses about their function. Either the head rotations serve to create unexpected situations and should ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…In some species of cercopithecines, head and torso rotations are body movements peculiar to play (Petrů et al, 2008), a pattern also present in many other mammalian lineages (e.g. Bekoff, 1974;Wilson & Kleiman, 1974;Byers, 1984;Donaldson et al, 2002).…”
Section: (3) Non-human Primatesmentioning
confidence: 88%
See 1 more Smart Citation
“…In some species of cercopithecines, head and torso rotations are body movements peculiar to play (Petrů et al, 2008), a pattern also present in many other mammalian lineages (e.g. Bekoff, 1974;Wilson & Kleiman, 1974;Byers, 1984;Donaldson et al, 2002).…”
Section: (3) Non-human Primatesmentioning
confidence: 88%
“…However, this underestimates the variety of different contexts and ways that different species can engage in self-handicapping. For example, a younger partner can engage in self-handicapping as well as its older partner (as occurs among dogs; Bauer & Smuts, 2007), and self-handicapping may also occur during solitary play when no partner is present (Petrů et al, 2008). Self-handicapping can arise as an animal orients its body in an unusual or unnatural position with respect to either its play partner or to the physical environment.…”
Section: Self-handicapping and Role Reversals As Aspects Of Communmentioning
confidence: 99%
“…The social play of an individual during an OU was defined by active interactions between the focal individual and another individual(s), such as play‐fighting, play‐chasing, “tug‐of‐war” with an object, or taking an object from a holder, at least once, as described in previous studies (Petrů, Špinka, Lhota, & Šípek, ; Shimada, ; Špinka et al, ; Symons, ; Thierry, ). Because these different types of play interactions often occur sequentially (Fagen, ; Shimada, ; Symons, ), it was not possible for the observer to distinguish which individual participated in which type of interaction in each moment, especially when more than three individuals played socially at once.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, vigorous and variable head rotations, torso twists and body pirouettes are among the most widely occurring elements of play (Byers, 1984). Petrů et al (2008) analysed the kinematics of play head rotations in Hanuman langurs (Presbytis entellus) and found that they include different, sometimes extreme positions of the head that follow each other in variable sequences; vision is most probably blurred during such rotations owing to the high angular velocities. Špinka et al (2001) specifically suggested that one major and widely present function of play is to train for unexpected situations and mishaps, i.e.…”
Section: Playmentioning
confidence: 99%